Exploration of Pediatric Cardiopulmonary Resuscitation: A conceptual paper - Hilmy Zaki, Farah Syazwani; Hashim, Noraini; Soo, Kok Wai; Widiyanti, Anggriana Tri (Environment-Behaviour Proceedings Journal, 2022)
Cardiopulmonary resuscitation (CPR) flow interventions are required as pediatric CPR tends to be chaotic, and documentation systems are inclined to adults. This paper presents the conceptual framework for exploring CPR and evaluating the Resuscitation Feedback Form of the Pediatric Intensive Care Unit Institut Jantung Negara. The theory of Planned Behaviour will be used in this study to explore team members’ thoughts about PICU CPR and documentation. The case study method will be used to explore two CPR events. The expected findings are the comments from team members on PICU CPR weaknesses and inputs in improving the documentation.